Stages and future of women’s health: A call for a life-course approach - Zohra S. Lassi; Jeannette M. Wade; Edward Kwabena Ameyaw (Women's Health)
Over the years, discourse on women’s health has skewed towards reproductive health, particularly on matters relating to maternal and child health, contraception, and pregnancy-related care. In spite of the relevance of these aspects, such a narrow perspective overlooks the broader spectrum of health concerns that affect women across different life stages, hence the need to refocus women’s health through the lens of the life-course perspective. The life-course perspective is a framework for understanding human development that centers on time and space. From adolescence to old age, women encounter a wide array of health challenges and experiences, including non-communicable diseases (NCDs), mental health disorders, musculoskeletal conditions, and the long-term consequences of early-life exposures. Addressing these issues requires a paradigm shift toward a more comprehensive and inclusive approach that recognizes the lifelong nature of women’s health needs. Rather than treating health issues in isolation, the life-course perspective considers how early-life exposures, social determinants, and lifestyle factors influence health trajectories over the life spectrum. For women, this means recognizing that adolescent health behaviors affect midlife disease risk, menopause has implications for cardiovascular and bone health, and older age brings unique challenges such as frailty and cognitive decline. This model underscores the importance of preventive care, early interventions, and tailored health services at every stage of life. Consequently, this editorial takes a life-course approach to highlight the dominant health and health-related realities of women, segmented into three cardinal phases: emerging adulthood, adulthood, and late adulthood. It concludes by drawing governments and the global community’s attention to the need to focus healthcare systems on universal, gender-sensitive healthcare policies that guarantee accessible, affordable, and high-quality services tailored to women’s needs at every stage of life. Policies and programs that support women at every stage of life must take center stage in the quest to create a future where all women, regardless of age or background, can achieve optimal health and well-being.